Pengaruh Keterampilan Digital dan Project-Based Learning terhadap Kesiapan Kerja Mahasiswa: Peran Mediasi Soft Skills - Faris Alfahad; Olivia Fachrunnisa (Lembaga Yasin AlSys, 2026)
The development of the Fourth Industrial Revolution has driven significant changes in the competencies required of the workforce, compelling universities to produce graduates who are not only academically strong but also possess comprehensive work readiness relevant to the dynamics of the industrial world. Students’ work readiness is influenced by digital skills, the implementation of project-based learning, and the mastery of soft skills that support adaptability, communication, and problem-solving abilities. This study aimed to analyze the influence of digital skills and project-based learning on students’ work readiness, with soft skills as a mediating variable. A quantitative approach with an explanatory design was employed involving 150 final-year students in Central Java selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results showed that digital skills and project-based learning had a positive and significant effect on soft skills. In addition, digital skills, project-based learning, and soft skills also had a positive and significant effect on students’ work readiness. Furthermore, soft skills were found to mediate the influence of digital skills and project-based learning on work readiness. These findings affirm that the integration of project-based learning and the strengthening of digital skills in higher education curricula play a strategic role in enhancing soft skills and graduates’ work readiness to face increasingly competitive labor market conditions.